Curing Characteristics, Tensile And Morphological Properties Of Tea Waste Filled Natural Rubber Composites - Hamdan, Nur Zafirah (Universiti Sains Malaysia, 2018)
The objective of this research work was to study the curing characteristics, tensile and morphological properties of tea waste filled natural rubber composites. The tea waste powder was characterized by using Fourier Transform Infra-Red (FTIR) Spectroscopy and Scanning Electron Microscopy (SEM) testing. Curing characteristics, tensile properties, morphological studies of tensile fractured surfaces and the extent of rubber-filler interactions of tea waste filled natural rubber (NR) composites were investigated as a function of filler loading in Series 1, the effect of silane coupling agent in Series 2 and the hybrid fillers between tea waste and carbon black in Series 3. The tea waste loading used in Series 1 and Series 2 was 0, 5, 10, 15, 30 phr and 0, 5, 10, 15 phr, respectively while in Series 3, the mixed of tea waste (TW) with carbon black (CB) was in the function of TW + CB which was 30 + 0, 30 + 10, 30 + 20 and 30 + 30 phr. The results indicate that the natural rubber composites without the presence of coupling agent which was Si69 (Series 1) has the poor interaction between tea waste powder hence reduced the properties of the composites while the natural rubber composites with the presence of Si69 (Series 2) showed the improvement in the properties of the composites as the better interaction occurred between rubber and filler. In Series 3, as the amount of carbon black increase, the properties of the natural rubber composites also increased due to the incorporation of reinforcing fillers in the rubber compounding that enhanced the rubber properties.